Long-Lasting Immunity Against SARS-CoV-2: Dream or Reality? - Gussarow, Daniel; Bonifacius, Agnes; Cossmann, Anne; Stankov, Metodi V.; Mausberg, Philip; Tischer-Zimmermann, Sabine; Gödecke, Nina; Kalinke, Ulrich; Behrens, Georg M. N.; Blasczyk, Rainer; Eiz-Vesper, Britta (Frontiers in Medicine, 2021)
Since its declaration as a pandemic in March 2020, SARS-CoV-2 has infected more than 217 million people worldwide and despite mild disease in the majority of the cases, more than 4.5 million cases of COVID-19-associated death have been reported as of September 2021. The question whether recovery from COVID-19 results in prevention of reinfection can be answered with a “no” since cases of reinfections have been reported. The more important question is whether during SARS-CoV-2 infection, a protective immunity is built and maintained afterwards in a way which protects from possibly severe courses of disease in case of a reinfection. A similar question arises with respect to vaccination: as of September 2021, globally, more than 5.2 billion doses of vaccines have been administered. Therefore, it is of utmost importance to study the cellular and humoral immunity towards SARS-CoV-2 in a longitudinal manner. In this study, reconvalescent COVID-19 patients have been followed up for more than one year after SARS-CoV-2 infection to characterize in detail the long-term humoral as well as cellular immunity. Both SARS-CoV-2-specific T cells and antibodies could be detected for a period of more than one year after infection, indicating that the immune protection established during initial infection is maintained and might possibly protect from severe disease in case of reinfection or infection with novel emerging variants. Moreover, these data demonstrate the opportunity for immunotherapy of hospitalized COVID-19 patients via adoptive transfer of functional antiviral T cells isolated from reconvalescent individuals.